Diagnostic accuracy of MRI in differentiating non-muscle invasive from muscle invasive bladder carcinoma taking histopathological staging as a standard - Syed Muhammad Faiq; Mehtab, Khujasta; Nazish Naz; Fatima Batool; Kiran Naz; Naqvi, Anwar; Hassan, Adeeb ul (International Journal of Endorsing Health Science Research, 2014)
To Determine Diagnostic accuracy Of MRI in differentiating non-muscle invasive from muscle invasive bladder carcinoma taking Histopathological staging as a standard. The data of 53 patients with bladder tumor who previously confirmed by cystoscopy were examined at 1.5 T, images were obtained and analyzed by radiologist without knowledge of the tumor stage. T2-weighted spin-echo or turbo-spin-echo, and dynamic Ti-weighted fast gradient-echo sequences were used. Histopathological grading served as standard of reference. Compared with the results submitted from the histopathology unit and using more detailed TNM classification, the sensitivity, specificity, and percent accuracy of MRI was 91%, 86%, 85% respectively. This data confirms the under-staging of the bladder tumor invasion done histopathologically while MR is a promising, non-invasive technique for the detection of bladder lesions with a high diagnostic performance.